Inter-island differentiation and contrasting patterns of diversity in the iconic Canary Island sub-alpine endemic Echium wildpretii (Boraginaceae). Issue 5 (4th July 2021) - Graham, Rachael E.; Reyes-Betancort, J. Alfredo; Chapman, Mark A.; Carine, Mark A.
Abstract : The sub-alpine zones of oceanic islands are unique and dynamic ecosystems with high levels of endemism, making them particularly suitable model systems in which to investigate evolutionary and biogeographic processes. The sub-alpine flora of the Canary Islands is restricted to the islands of Tenerife and La Palma. Its origins are poorly understood. Echium wildpretii Hook.f. is an iconic species of the subalpine zones of these two islands, with distinct subspecies recognized on each island. This study examines patterns of genetic and morphological diversity in E. wildpretii to investigate the diversity and evolution of the lineage. Nine microsatellite markers were designed and used to investigate population genetic structure and patterns of gene flow within and between islands and populations. Morphological characters were assessed to test the distinctiveness of the two subspecies recognized. Strong genetic differentiation was observed between islands with higher genetic diversity on the younger island of La Palma than on Tenerife. Very low levels of inter-island gene flow were observed indicating that these taxa are reproductively isolated and evolving independently. Morphological analysis confirmed the distinctiveness of plants from the two islands. Given their genetic and morphological distinctiveness the taxa on Tenerife and La Palma merit recognition as distinct species. Higher genetic diversity in the La Palma species is consistent with an origin of the lineage on this island via upslope colonization, followed by dispersal to Tenerife where the plants show lower genetic diversity.